The Unstable Elbow An Evidence-Based Approach to Evaluation and Management - Tashjian, Robert Z.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Providing a detailed review of one of the most common clinical problems, elbow instability, this comprehensive text organizes the most up-to-date, evidence-based information on the rapidly advancing field of elbow surgery. Initial chapters focus on anatomy, biomechanics and the most currently utilized surgical approaches for the treatment of the unstable elbow. Subsequent chapters focus on the evaluation and surgical treatments of acute instabilities, such as simple dislocations and fracture-dislocations, as well as chronic instabilities, including chapters focusing on the non-operative and operative management of the throwing athlete. The final chapters describe additional treatment strategies for complex instabilities, focusing on external fixation, total elbow arthroplasty and elbow fusion. Each chapter includes background information, an evaluation section, a treatment algorithm, non-operative treatment strategies, surgical management, published outcomes and preferred methods of treatment from each author. A supplemental video section is also included, depicting frequently performed procedures. Written by experts in the field, The Unstable Elbow consolidates all of the current knowledge of elbow instability into a valuable resource for orthopedic surgeons and residents worldwide.
Part I: Anatomy and Biomechanics of the Elbow -- Anatomy of the Elbow -- Biomechanics of the Elbow -- Surgical Approaches to the Elbow -- Part II: Acute Instabilities of the Elbow -- Treatment of Simple Elbow Dislocations -- Management of Terrible Triads -- Varus Posteromedial Rotatory Instability -- Posterior Monteggia Fracture-Dislocations -- Transolecranon Fracture-Dislocations -- Treatment of Longitudinal Forearm Instability: Essex-Lopresti Injury -- Part III: Chronic Instabilities of the Elbow -- Evaluation and Management of Posterolateral Rotatory Instability (PLRI) -- Evaluation and Nonoperative Treatment of the Unstable Throwing Elbow -- Operative Strategies for Ulnar Collateral Ligament Insufficiency -- Treatment of Combined Medial and Lateral Collateral Ligament Insufficiency -- Treatment of the Chronically Subluxated Elbow (Persistent Elbow Instability) -- External Fixation in the Setting of Elbow Instability -- The Role of Total Elbow Arthroplasty in the Setting of Elbow Instability -- Elbow Fusion for The Unstable Elbow. .
Keywords: Medicine; Rheumatology; Orthopedics; Sports medicine; Medicine & Public Health; Orthopedics; Sports medicine; Rheumatology